Endymion Spring - Skelton, Matthew 1971- (Delacorte Press, 2006)
Having reluctantly accompanied his academic mother and pesky younger sister to Oxford, twelve-year-old Blake Winters is at loose ends until he stumbles across an ancient and magical book, secretly brought to England in 1453 by Gutenberg's mute apprentice to save it from evil forces, and which now draws Blake into a dangerous and life-threatening quest